2023
DOI: 10.3389/fpubh.2022.1101817
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 risk, attitudes and behaviour study (CRAB study): A knowledge, attitudes, and practise qualitative study of COVID-19 in the Royal Navy

Abstract: IntroductionOutbreaks of SARS-CoV-2 onboard maritime platforms spread rapidly and have high attack rates. The aim of the COVID-19 Risk, Attitudes and Behaviour (CRAB) study was to investigate the knowledge, attitudes, and practises in the Royal Navy in relation to COVID-19 prevention.MethodsThe CRAB study was a cross-sectional survey, using a census sampling method, conducted in May and June 2021. An online questionnaire was distributed to all serving Royal Navy regular personnel using either the MyNavy applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In fact, previous studies have shown that attitude toward and knowledge of blood donation serve as key factors that affect continuous participation in blood donation ( 21 , 22 ). Attitude is a key factor in predicting behavior in general ( 23 , 24 ). In Kim and Yoon ( 22 ) and France et al ( 25 ) it was reported that positive attitude toward blood donation affects donation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, previous studies have shown that attitude toward and knowledge of blood donation serve as key factors that affect continuous participation in blood donation ( 21 , 22 ). Attitude is a key factor in predicting behavior in general ( 23 , 24 ). In Kim and Yoon ( 22 ) and France et al ( 25 ) it was reported that positive attitude toward blood donation affects donation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect support of the latter option is provided by assessments of the beliefs and attitudes of military personnel towards the COVID-19 pandemic, which showed that the spectrum of attitudes was considerable and, by far, not all soldiers considered the diseaseassociated threat as serious [20,21]. It is likely that negative attitudes towards restrictive infection control measures might have been facilitated by the fact that soldiers were much less endangered than civilians by COVID-19 in terms of both the need for intensive care treatment and death [22], which is a typical "healthy worker effect".…”
Section: Introductionmentioning
confidence: 99%